Indikator pH Ekstrak Bunga Rosella untuk Mendeteksi Kesegaran Filet Ikan Nila pada Suhu Chiller - Deli Silvia; Muhammad Fajar; Wiwi Prastiwinarti (Universitas Sriwijaya, 2022)
Tilapia is a food product that has high nutritional value so that it is favored by the people of Indonesia. However, tilapia has a short shelf life. The way to extend the shelf life is to pack the tilapia but it is difficult for consumers to know the level of freshness of the tilapia. The purpose of this study was to determine the color change of smart indicator labels using rosella flower extract to detect the freshness of tilapia filets at a chiller temperature of ± 40C by using pH variations of label color indicators, namely 3, 5, 7, and 9. pH test, organoleptic test, and mean RGB label. The research method used is a Completely Randomized Design (CRD) method which consists of two repetitions in each test. The test was carried out for 9 days and was tested every 3 days. The results showed that the appropriate color indicator label to detect the freshness of fish fillets was pH 9 and pH 7 on day 6 because the color indicator label changed from dark brown to light brown. At pH 3 and 5, there was no visible color change. The highest pH value of tilapia fillet at cold storage temperature was 7.14 and the lowest pH was 6.46. In addition, the organoleptic value of the tilapia filet was not fresh on the 6th day.